# $(a)$ From the sum of $3x-y+11$ and $-y-11$ subtract $3x-y-11$.$(b)$ From the sum of $4+3x$ and $5-4x+2x^2$ subtract the sum of $3x^2-5x$ and $-x^2+2x+5$.

#### Complete Python Prime Pack

9 Courses     2 eBooks

#### Artificial Intelligence & Machine Learning Prime Pack

6 Courses     1 eBooks

#### Java Prime Pack

9 Courses     2 eBooks

To do: $(a)$. To subtract $3x-y-11$ from the sum of $3x-y+11$ and $-y-11$.

$(b)$. To subtract the sum of $3x^2-5x$ and $-x^2+2x+5$ from the sum of $4+3x$ and $5-4x+2x^2$.

Solution:

a). The sum of $3x-y+11$ and $-y-11$.

$=(3x-y+11)+(-y-11)$

$=3x-y+11-y-11$

$=3x-2y$

Now, we subtract $3x-y-11$ from $3x-2y$

$(3x-2y)-(3x-y-11)$

$=3x-2y-3x+y+11$

$=-y+11$

b). The sum of $4+3x$ and $5-4x+2x^2$.

$=(4+3x)+(5-4x+2x^2)$

$=4+3x+5-4x+2x^2$

$=-x+2x^2+9$

Sum of $3x^2-5x$ and $-x^2+2x+5$

$=(3x^2-5x)+(-x^2+2x+5)$

$=3x^2-5x-x^2+2x+5$

$=2x^2-3x+5$

Now, we subtract $-x+2x^2+9$ from $2x^2-3x+5$

$=2x^2-x+9-2x^2+3x-5$

$=2x+4$
Updated on 10-Oct-2022 13:38:20